PENGOPERASIAN KEMBALI RIBUAN KINCIR AIR DI SUMATERA BARAT MELALUI PENGEMBANGAN SISTEM KINCIR TEKNOLOGI CROSS FLOW (KATCF) - Asep Neris Bachtiar; Gamindra Jauhari; Hendri Sawir (LP2M - Institut Teknologi Padang, 2014)
Not water wheel operation of thousands of them in West Sumatra caused by many conditions that have an old windmill and broken while the quality of wood raw material to rebuild the water wheel increasingly difficult to obtain even if there are very expensive. In an effort to facilitate community rebuild water wheel plant, researchers had the idea to make modifications to the system of wheel revolution. In the process of this research turbine modification will replace the wood material into a material such as steel plate steel, U steel, steel elbow, steel shaft and are easily available in the market at affordable prices. Besides, in this modification process will adopt a touch of cross flow turbine technology to be applied to the wheel under study. From the results of testing the efficiency of prime movers KATCF known trend of relatively constant efficiency for each of the percentage change in discharge initiated discharge 25% to 100%. The percentage of discharge 100% or 100 liters/s obtained an efficiency of 51%. Thus, the quality of prime movers KATCF built quite satisfactory and can be proud of.